A Propensity Score-matched Comparison of Infliximab and Adalimumab in Tumour Necrosis Factor-α Inhibitor-naïve and Non-naïve Patients With Crohn's Disease: Real-Life Data From the Sicilian Network for Inflammatory Bowel Disease. (6th October 2018) - Macaluso, Fabio Salvatore; Fries, Walter; Privitera, Antonio Carlo; Cappello, Maria; Siringo, Sebastiano; Inserra, Gaetano; Magnano, Antonio; Di Mitri, Roberto; Mocciaro, Filippo; Belluardo, Nunzio; Scarpulla, Giuseppe; Magrì, Giovanni; et al.
Abstract: Background and Aims: There is an unmet need to better understand the effectiveness of different biologics in inflammatory bowel diseases. We aimed at performing a multicentre, real-life comparison of the effectiveness of infliximab [IFX] and adalimumab [ADA] in Crohn's disease [CD]. Methods: Data of consecutive patients with CD treated with IFX and ADA from January 2013 to May 2017 were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Disease. We used propensity score-matching accounting for the main baseline characteristics in TNF-α inhibitor-naïve and non-naïve patients. Results: A total of 632 patients [735 total treatments] were included. Among naïve patients, a clinical benefit [the sum of steroid-free remission plus clinical response] was achieved in 81.8% patients treated with ADA and in 77.6% patients treated with IFX (adjusted odds ratio [OR]: 1.23, 95% CI 0.63-2-44, p = 0.547] at 12 weeks; after 1 year, a clinical benefit was achieved in 69.2% of patients treated with ADA and in 64.5% patients treated with IFX [adjusted OR: 1.10, 95% CI 0.61–1.96, p = 0.766]. Among non-naïve patients, a clinical benefit was achieved in 61.7% of patients treated with ADA and in 68.1% of patients treated with IFX [adjusted OR: 0.72, 95% CI 0.21–2.44, p = 0.600] at 12 weeks; after 1 year, a clinical benefit was achieved in 48.9% of patients treated with ADA and in 40.4% patients treated with IFX [adjusted OR: 1.23, 95% CI 0.54–2.86, p = 0.620]. Conclusions: In this propensity score-matched comparison of ADA and IFX in CD, both drugs showed high rates of clinical benefit, without significant differences between them.